The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1016/j.ygyno.2014.08.015
|View full text |Cite
|
Sign up to set email alerts
|

Oxysterols synergize with statins by inhibiting SREBP-2 in ovarian cancer cells

Abstract: Objective Determine mechanisms responsible for enhanced statin efficacy in a novel statin combination we name STOX (STatin–OXysterol). Methods Ovarian cancer cell lines were treated with combinations of statins and oxysterols. Cell viability was determined by a modified MTT assay. Apoptosis was evaluated by immunoblotting of PARP and DAPI-mediated visualization of apoptotic nuclei. STOX effects on the expression of genes of the mevalonate pathway were assessed by real-time qPCR and immunoblotting. siRNA-medi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 35 publications
2
22
0
Order By: Relevance
“…Hence, inhibition of HMGCR and SREBPs would increase responsiveness to drugs (144). The same drug resistance mechanism related to SREBPs and lipid metabolism was also found in breast tumors, multiple myeloma, glioblastoma, lung tumors, and liver tumors (22,58,77,(145)(146)(147), as well as antitumor drugs, including cisplatin (148), rapamycin, epidermal growth factor receptor-targeted inhibitors and docetaxel (57,147,149). Natural drugs combined with traditional anti-tumor drugs to increase the sensitivity of cells to treatment are very promising.…”
Section: Provide Protection For Tumor Cellsmentioning
confidence: 77%
“…Hence, inhibition of HMGCR and SREBPs would increase responsiveness to drugs (144). The same drug resistance mechanism related to SREBPs and lipid metabolism was also found in breast tumors, multiple myeloma, glioblastoma, lung tumors, and liver tumors (22,58,77,(145)(146)(147), as well as antitumor drugs, including cisplatin (148), rapamycin, epidermal growth factor receptor-targeted inhibitors and docetaxel (57,147,149). Natural drugs combined with traditional anti-tumor drugs to increase the sensitivity of cells to treatment are very promising.…”
Section: Provide Protection For Tumor Cellsmentioning
confidence: 77%
“…Knockdown of CYP7B1 in an apolipoprotein E (apoE) atherosclerotic mouse model leads to elevated inflammation and accelerated atherosclerotic lesion formation [33]. Similarly, in vitro studies have shown that direct treatment of macrophages with 27HC increases IL-6, TNF-α and IL-1β expression [3436]. Mechanistically, 27HC drives the M1 phenotype in macrophages through the estrogen receptor alpha [30].…”
Section: Impact Of Lipids On Macrophage and T Lymphocyte Phenotypesmentioning
confidence: 99%
“…Desmosterol is the most prevalent sterol in atherosclerotic plaques and is a ligand for both LXR and SREBP [3134]. When macrophages have elevated intracellular cholesterol, desmosterol metabolism is inhibited, leading to elevated desmesterol.…”
Section: Impact Of Lipids On Macrophage and T Lymphocyte Phenotypesmentioning
confidence: 99%
“…We and others have demonstrated a restorative feedback loop by induction of the statin targeting enzyme, the HMGCR, as a mediator of statin resistance in human breast and prostate cancer as well as multiple myeloma cells [ 52 , 79 , 80 ]. Similar mechanisms might occur in ovarian cancer cells, especially as cisplatin and simvastatin induce a strong accumulation of HMGCR in ovarian cancer cells [ 81 , 82 ]. In times of personalized medicine, it would be greatly relevant to identify patients with those molecular subtypes, that would mostly benefit from a statin or N-BP therapy, individually or in combination with chemotherapy, as well as to define the optimal therapeutic window.…”
Section: Discussionmentioning
confidence: 96%